Kinesio Taping vs. Auricular Acupressure for the Personalised Treatment of Primary Dysmenorrhoea: A Pilot Randomized Controlled Trial - Elena Mejías-Gil (Journal of Personalized Medicine, 2021)
Background: Dysmenorrhoea is the medical term for menstrual pain. The World Health Organization estimates that up to 81% of women of childbearing age are affected by this condition, and it is one of the leading causes of absenteeism from work and school among women. Although there are pharmacological treatments available for menstrual-pain relief, they do not respond to all women’s needs. Therefore, there is a need to study and develop non-pharmacological alternatives to broaden the individualised treatment options for dysmenorrhea. There are scarce studies published on non-pharmacological treatments, such as kinesio tape and auricular acupressure for the relief of menstrual pain, but the scientific evidence available suggest that these techniques may be beneficial in addressing this problem. The objective of this pilot study was to assess and compare the effectiveness of kinesio tape and auricular acupressure to decrease pain and drug intake in women with primary dysmenorrhoea. Methods: This was a double-blind randomized clinical controlled trial. The period of study was from September 2017 to August 2018. Women enrolled in the University of Extremadura and who had primary dysmenorrhoea were randomized to five groups: control (n = 23), kinesio tape (n = 23), placebo kinesio tape (n = 23), auricular acupressure (n = 23) and placebo auricular acupressure (n = 22). Measures were taken during the pretreatment phase (at four menstrual cycles), during the post-intervention phase (at four menstrual cycles) and during the follow-up phase (at the first and third menstrual cycles after the treatment was completed). The primary outcome measures were mean pain intensity, maximum pain intensity, number of painful days and dose of drug intake during menstruation, measured with the Visual Analogue Scale. The secondary outcome measures were the length of the cycle, the length of menstruation, the drug intake and the type of drug. Results: In all, 108 participants completed the study. The statistical analysis (MANOVA, ANOVA, t-paired and McNemar tests) showed that kinesio tape and auricular acupressure have a beneficial effect on pain relief (mean pain intensity, p < 0.001; maximum pain intensity, p < 0.001; number of painful days, p = 0.021; dose of drug intake, p < 0.001). In addition, once the treatments were withdrawn, the auricular-acupressure group maintained lower scores during the first follow-up cycle (p < 0.001). Conclusions: Kinesio tape and auricular acupressure decrease pain and drug intake in women with primary dysmenorrhoea. The changes in the auricular-acupressure group seemed to last longer. The results suggest that these techniques could be used as complementary personalised therapies to the pharmacological treatment and not as a substitution.